Paciente de sexo femenino de 70 años de edad con desnutrición. - Zúñiga Arias, Ilen Yamilet (2020)
The present clinical case is about a 70-year-old female patient with malnutrition, who attends a medical consultation with a family member due to pain in the hands, marked weight loss, anorexia and asthenia, and difficulty walking. Leptosomatic biotype is observed, pale facies, sunken eyes, dry mucous membranes, thinning of the face, loss of muscle mass is observed in the upper limbs. The anthropometric, biochemical, clinical and dietary nutritional evaluation is carried out, where he presents an estimated weight of 47kg with a height of 151 cm and a body mass index of 20.62 kg/m2, within the biochemical tests he presents alteration of the protein indicators total with 6g/ l and albumin of 3.1g/dl. The objective of this case study is to improve nutritional status, where it is intervened with the prescription of a diet of 1700 kilocalories hyperprotein with nutritional supplementation of polymeric formula fractionated in 5 meal times. As a conclusion, follow-up and monitoring is given where the nutritional status of the patient is improving according to the evaluated indicators, there is a weight gain in 3 months with a considered increase in the body mass index, biochemical values of albumin and total proteins within the parameters normal, improved clinical signs and adequate supply of nutrients with the supplementation of polymeric formula.